CONSIDERATIONS REGARDING PHYSICAL TRAINING IN HANDBALL - Timofte Mihai; Leuciuc Florin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
The training orientation of handball players should be carried out in the direction of the improvement and efficient execution of the short and explosive actions because, as it is the main way of progress in the contemporary handball. It is considered that a proper physical preparation is crucial for the enforcement and improvement of the technical training, moreover, it determines the achievement of tactical training. In top level sports for seniors it should be underlined the fact, that the development level of strenght influences the manifestation degree of other motor qualities, and also, the quality and efficiency of the technical and tactical executions, all these aspects building a complex methodic approach of its development.Training for strength purpose comprises not only the raising of maxim indicators of strength qualities but also, comprises the improvement of the capacities for their use in the process of the competitional activity, that is based on the development optimization degree of the strength qualities and the improvement of the sport technique.The purpose of the study was to identify some aspects of the physical training specific for handball game in the current period time with emphasis on motor skill development - strength. In conducting this study, I have utilized a series of methods that served to formulate some strength conclusions useful for the experimental research: the study of special literature, the comparative method, the analyzing and interpreting data method in order to make an objective analysis of the current situation regarding the training of handball players. Obtaining sports performance is conditioned by achieving an optimal level for each component of sports training in accordance with the individual and group potential, the training level and the established training and competition objectives.